To Be a (Blended) B-Teacher in the 21st Century – Some Reflections - dos Reis, António Manuel Diogo (International Journal of Research in E-learning, 2020)
<span style="text-align: justify; color: rgb(51, 51, 51); text-transform: none; text-indent: 0px; letter-spacing: normal; font-family: Lato; font-size: 14px; font-style: normal; font-weight: 400; word-spacing: 0px; float: none; display: inline !important; white-space: normal; orphans: 2; widows: 2; background-color: rgb(242, 242, 242); font-variant-ligatures: normal; font-variant-caps: normal; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial;">Being a teacher in the 21st century is a great challenge and requires great thought. A big evolution has happened over the last 70 years. From a room computer (the Mark I in 1943) to tiny pocket computers, thousands of times smaller and thousands of times bigger in performance and capacity. E-learning 3.0 is based on synchronous interactivity and it was only possible after 2004 due to a considerable increase of Internet bandwidth available, evolution in video compression, stream video, and sophistication of virtual classroom platforms. This was another revolution. As a result, e-learning has evolved to a new form: b-learning – where students will never be alone and interactivity becomes very important. B-learning has a different format now: from now on it is asynchronous (content on demand and activities to be implemented in an interactive format with remote collaborative work) and synchronous in presence or virtual environment. Teachers need to evolve from teacher to (blended) b-teacher or b-tutor, offering a mixed teaching expertise.